Voyage - Ward, Julian; Lesko, Katie; Lueck, Amanda; Rupe, Trevor; Sledge, Ben (My University, 2014)
Premiere performance of flute quartet by ECU student composer Julian Ward. Recorded at A.J. Fletcher Recital Hall on November 20th, 2014.
Composer: Julian Ward.
Keywords: Woodwind quartets (Flutes (4))